2022
DOI: 10.3390/metabo12090835
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Selected Secondary Metabolites and Antioxidant Activity of Valerian and Lovage Grown in Organic and Low-Input Conventional System

Abstract: In the present study, the roots of valerian (Valeriana officinalis L.) and lovage (Levisticum officinale Koch.) from the organic and low-input conventional cultivation systems were subjected to the analysis of selected groups of phenolic compounds (phenolic acids, flavonoids) and antioxidant activity. Plants were grown in two consecutive vegetation seasons in the experimental plots located in western Poland. Phenolic acids and flavonoids were determined by high performance liquid chromatography (HPLC/UV–Vis), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…Acid 4 has been previously found in the herbal part of lovage [ 12 , 14 , 15 , 31 ], and the remaining phenolics have been discovered for the first time in L. officinale . A previous report [ 29 ] showed that some flavonoid compounds can be detected in lovage roots; however, in our case, no member of this group was found.…”
Section: Resultscontrasting
confidence: 83%
See 2 more Smart Citations
“…Acid 4 has been previously found in the herbal part of lovage [ 12 , 14 , 15 , 31 ], and the remaining phenolics have been discovered for the first time in L. officinale . A previous report [ 29 ] showed that some flavonoid compounds can be detected in lovage roots; however, in our case, no member of this group was found.…”
Section: Resultscontrasting
confidence: 83%
“…Subsequently, approximately 20 representatives of the phtalides group were isolated from the plant [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] ( Table 1 ). Further investigation led to detection of polyynes, mono- and sesquiterpenes, phenolics, and other groups [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation